(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To determine the efficacy and rank the superiority of various traditional herbal medicine dosage forms in improving tumor size and disease control. Literature Search and Review: A systematic review and network meta-analysis were conducted using five databases (PubMed, Cochrane, Web of Science, Google Scholar, and CNKI) up to December 2025. Results: Combining traditional herbal medicine significantly improved tumor size (OR = 1.77; 95% CI: 1.46 – 2.14) and disease control (OR = 1.88; 95% CI: 1.53 – 2.32) compared to the control group. Network analysis identified that traditional herbal medicine decoction combined with standard treatment was the most superior intervention for tumor size improvement (OR = 1.35; 95% CI: 1.24 – 1.48; SUCRA 79.62%). Regarding the disease control rate, decoction combined with standard treatment was the most superior intervention (OR = 1.12; 95% CI: 1.08 – 1.17; SUCRA 84.85%), while decoction alone only showed a positive trend without reaching statistical significance (OR = 1.23; 95% CI: 1.00 – 1.51; SUCRA 79.85%). Conclusion: Traditional herbal medicine is significantly effective in improving tumor size and stabilizing the disease. Specifically, the decoction form demonstrates overwhelming superiority and should be prioritized for integration into multimodal treatment protocols for cancer patients.